2019
DOI: 10.1093/jn/nxz098
|View full text |Cite
|
Sign up to set email alerts
|

Prediagnostic Proinflammatory Dietary Potential Is Associated with All-Cause Mortality among African-American Women with High-Grade Serous Ovarian Carcinoma

Abstract: Background Chronic inflammation is associated with ovarian carcinogenesis; yet, the impact of inflammatory-related exposures on outcomes has been understudied. Objective Given the poor survival of women diagnosed with ovarian cancer, especially African-Americans, we examined whether diet-associated inflammation, a modifiable source of chronic systemic inflammation measured by the dietary inflammatory index (DII), was associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…We failed to show that the effect of the E-DII on all-cause mortality in breast cancer survivors differed between smokers and non-smokers; a study focusing on high-grade serous ovarian carcinoma found a protective effect of anti-inflammatory diet on all-cause mortality risk among smokers 31 . Biologically, cigarette smoke contains many oxidants and free radicals and pro-inflammatory compounds that may activate endogenous mechanisms such as recruitment of neutrophils and macrophages to further increase the oxidant injury 40 .…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…We failed to show that the effect of the E-DII on all-cause mortality in breast cancer survivors differed between smokers and non-smokers; a study focusing on high-grade serous ovarian carcinoma found a protective effect of anti-inflammatory diet on all-cause mortality risk among smokers 31 . Biologically, cigarette smoke contains many oxidants and free radicals and pro-inflammatory compounds that may activate endogenous mechanisms such as recruitment of neutrophils and macrophages to further increase the oxidant injury 40 .…”
Section: Discussionmentioning
confidence: 83%
“…However, they used the DII (not the E-DII) and did not consider dietary supplements 19 . Three studies 29 31 considered other cancer types in relation to post-diagnosis E-DII score on the risk of mortality, however, a post-diagnosis proinflammatory diet was not statistically significantly associated with mortality risk in cancer patients. Relatively short-term follow-up time and retrospective study designs maybe contribute to above-mentioned null results, which are similar to what we found when we examined the short duration (≤15 person-years) subgroup.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our approach evaluates how multiple factors can affect EOC survival through three levels: environmental (from neighborhood-level and census tract factors), individual (from data collected during interviews with each participant), and cellular (tumor immunity). In AACES we focus on in ammatory factors, given the strong role of in ammation in ovarian carcinogenesis and growing evidence of its role in prognosis [5].Given its size, geographical diversity, and breadth of data including biospecimens, the AACES cohort provides a unique resource to advance understanding of the multi-factorial causes of the ovarian cancer survival disparity in Black women. This information can in turn provide the foundational information needed to develop strategies to reduce and eventually eliminate this disparity.…”
mentioning
confidence: 99%
“…Our approach evaluates how multiple factors can affect EOC survival through three levels: environmental (from neighborhood-level and census tract factors), individual (from data collected during interviews with each participant), and cellular (tumor immunity). In AACES we focus on in ammatory factors, given the strong role of in ammation in ovarian carcinogenesis and growing evidence of its role in prognosis [5].…”
mentioning
confidence: 99%